Traditional Roles of African Women in Peace Making and Peace Building: An Evaluation - Ibok, Anweting Kevin; Ogar, Ogar Tony (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
The study set out to scrutinize the scope of conflict in Africa and further evaluate the contribution of women to the peace process as well as the challenges such roles impose on them. The study affirms the important roles of women as an agent of peace in which they demonstrated an act of courage and love to end conflicts when men failed. The study shows that there is an overemphasis on women as victims of conflict or sometimes as combatants or agents. This largely conceals the invaluable contribution of women to the peace process. This position amounts to placing them in a position that they might be seen as weaklings or perpetrators of conflict. The study further concludes that most of the conflicts that became protracted and deeprooted reflect institutional failure and the refusal of those in the position of authority to act at the right time due to greed, poverty, and lack of inclusive arrangement in governance. The study, therefore, recommends that the root of the problem must first be attacked in that government must be proactive enough to monitor, act promptly to diffuse tension in explosive issues that could lead to direct violence. This is achievable if the government is sincere, honest, and adopts an inclusive approach in governance thereby ensuring fairness in the distribution of resources.